2021
DOI: 10.2106/jbjs.20.01475
|View full text |Cite
|
Sign up to set email alerts
|

Limited Evidence for Biological Adjuvants in Hindfoot Arthrodesis

Abstract: Background:The purpose of the present study was to evaluate the efficacy of biological adjuvants in patients managed with hindfoot arthrodesis.Methods:A systematic review of the PubMed and Embase databases was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines with use of specific search terms and eligibility criteria. Assessment of evidence was threefold: level of evidence by criteria as described in The Journal of Bone & Joint Surgery, quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…47 Another meta analysis concluded that insufficient data are available to recommend the use of PDGF-derived biologics over bone autografts in hindfoot fusion. 39…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Another meta analysis concluded that insufficient data are available to recommend the use of PDGF-derived biologics over bone autografts in hindfoot fusion. 39…”
Section: Discussionmentioning
confidence: 99%
“…47 Another meta-analysis concluded that insufficient data are available to recommend the use of PDGF-derived biologics over bone autografts in hindfoot fusion. 39 Despite the potential to optimize bone healing, orthobiologic augmentation is rarely used for primary surgical fixation of acute fractures. 7,43 This is attributable to the satisfactory union rates and times to union using wellestablished fracture fixation methods without orthobiologic augmentation.…”
Section: Discussionmentioning
confidence: 99%